A Comparative Study of the Level of Depression among Students in the Hostel at Anbar University - Marwan Abdullatif (Journal of Global Pharma Technology, 2018)
Depression is one of the most common psychiatric diseases in the world, confirmed by global research. The World Health Organization (WHO) sees it as the second most important cause of death and disability in the world after heart disease by 2020. Depression is defined as